Etnobotânica de quintais em três comunidades ribeirinhas na Amazônia central, Manaus-AM - Souza, Célia Cristina Valero (Instituto Nacional de Pesquisas da Amazônia - INPA, 2010)
In the Amazon there are several production systems and land use that have been developed over many years by indigenous and caboclos, mainly for subsistence purposes. The homegardens represent one of these systems and are constituted of productive units where trees, shrubs and herbs are grown close to home. Besides being important reserves of useful plants, the homegardens can also reveal many aspects of local cultural history, being an excellent source of ethnobotanical information. The aim of this study was to characterize, from the ethnobotanical approach, homegardens of communities Agrovila and Julião, in the Sustainable Development Reserve Tupé, and homegardens of community Caioé, in the Rio Negro State Park (South Sector) - Central Amazon, Manaus (AM), as the composition and the uses of plant species useful. We randomly selected 54 homegardens in the three communities and have been semi-structured interviews and guided tours, with the residents to survey the socio-economic information on the plant species and useful collection of botanical material. Plant species were grouped into categories of use, as cited by respondents, and were calculated the diversity index of Shannon-Wiener, Jaccard similarity, the use value of species (VU) and agreement regarding the use of primary (CUP). Were recorded 266 species of plants deemed useful by the residents, belonging to 77 families. Families who stood out in number of species were Araceae, with 14, Arecaceae, with 13, Asteraceae with 12, Malvaceae with 10 and Lamiaceae with 9 species. Of this total, 45% are used in food, 35% in folk medicine and 33% as ornamentals. There is predominance the fruit species of food among, representing 63.3% of the total species in this category of use. The predominance of species used in feeding underscores the importance of homegardens in the food security of the community area. Was calculated the value in use (VU), obtaining as most commonly used species, consequently the most important, Mangifera indica L. (Anacardiaceae), Anacardium occidentale L. (Anacardiaceae) and Persea americana Mill. (Lauraceae). Among the species used in folk medicine, the highest rates of VU are Carapa guianensis Aubl. (Meliaceae), Arrabidaea chica (Humb. & Bonpl.) B. Verl. (Bignoniaceae) and Mangifera indica L. (Anacardiaceae). The calculation of the CUP showed was consensus on the use of Mangifera indica L. (Anacardiaceae) 84,9%, Inga edulis Mart. (Fabacaeae - Mimosoideae) 83,9% and Persea Americana Mill. (Lauraceae) 75,8% in the feeding, while the same calculation for the medicinal species pointed use concordance for the species Lippia alba (Mill.) NE Br. (Verbenaceae), with 84,6% and Cymbopogon citratus (DC.) Stapf (Poaceae), 48,6% as soothing and species Persea americana Mill. (Lauraceae), with 44,2% concordance in the use against anemia. With regard to the socio-economic, population surveyed consisted of 46 females (85.2%) and 8 men (14.8%), with ages between 15 and 68 years, of which 62.9% (34) has less than 50 years. Most are from the state of Amazonas (81.5%), low education level, and 74% had never studied or did not finish elementary school. The knowledge about plants and their uses is transmitted in 65% often from father to son, or from grandparents to grandchildren, both orally and 67% of respondents reported to be keeping this type of transmission to their children. In the perception of 57.4% of respondents, the homegarden is what was left after the construction of the house and that is in this environment (sides, back and front) and are considered important for providing food, shade, rest area and leisure.
Keywords: Etnobotânica; Plantas úteis da Amazônia; Comunidades ribeirinhas